2019
DOI: 10.1097/eja.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia care team improves outcomes in surgical patients compared with solo anaesthesiologist

Abstract: BACKGROUND In anaesthesiology, little attention has been drawn to the role of anaesthesia nurses as support personnel on quality of care. OBJECTIVES To compare an anaesthesiologist alone (solo anaesthesiologist) with an anaesthesia care team (anaesthesiologist and anaesthesia nurse). DESIGN An observational study. SETTING A single centre study. PARTICIPANTS Anaesthesiologists and anaesthesia nurses. INTERVENTION Anaesthesia performed by solo anaesthesiologists compared with anaesthesia care teams. MAIN OUTCOME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The second independent factor of interest consisted on the presence of an anaesthetic nurse. This is also consistent with a recent study in adults that found that the presence of a team consisting on a physician and nurse anaesthesiologists, in comparison with a solo anaesthesiologist, was associated with a 30 days decrease in mortality (22). The reasons advocated for explaining the results obtained in the latter were the optimisation of intraoperative care with a resulting long-lasting improvement in the overall outcomes, and the same explanation can also apply to our finding.…”
Section: Perioperative Complications and Human Resources Associated W...supporting
confidence: 93%
“…The second independent factor of interest consisted on the presence of an anaesthetic nurse. This is also consistent with a recent study in adults that found that the presence of a team consisting on a physician and nurse anaesthesiologists, in comparison with a solo anaesthesiologist, was associated with a 30 days decrease in mortality (22). The reasons advocated for explaining the results obtained in the latter were the optimisation of intraoperative care with a resulting long-lasting improvement in the overall outcomes, and the same explanation can also apply to our finding.…”
Section: Perioperative Complications and Human Resources Associated W...supporting
confidence: 93%
“…When these findings are considered, it is important to judge increased overlap balanced against potential efficiency and access benefits to assess how much overlap may be appropriate. This study is limited to physician-led anesthesiologist care teams; previous studies have shown that anesthesiology care teams improve outcomes compared with anesthesiologists working alone . Fifth, this study did not investigate operations with anesthesiologists supervising physicians in training by limiting resident involvement to less than 25% in each operation.…”
Section: Discussionmentioning
confidence: 99%
“…This study is limited to physician-led anesthesiologist care teams; previous studies have shown that anesthesiology care teams improve outcomes compared with anesthesiologists working alone. 36 Fifth, this study did not investigate operations with anesthesiologists supervising physicians in training by limiting resident involvement to less than 25% in each operation. Sixth, routinely collected electronic health record data have known limitations, which were mitigated by the MPOG registry's strict data quality controls.…”
Section: Limitationsmentioning
confidence: 99%
“…In a study of the University Hospital of Charleroi in Belgium, post-operative mortality rates within 30 post-operative days were 1.1% [ 2 ]. In this hospital, risk factors of post-operative mortality were identified as the absence of an anesthesia nurse, American Society of Anesthesiologists scores (ASA scores) > 2, emergency, duration of surgery and rate of admission to critical care unit [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%